PECAM1 Combines With CXCR4 to Trigger Inflammatory Cell Infiltration and Pulpitis Progression Through Activating the NF-κB Signaling Pathway - Liu, Yonghong; Zhang, Zhiyong; Li, Wenjing; Tian, Songbo (Frontiers in Cell and Developmental Biology, 2020)
Pulpitis is a frequent bacterially-driven inflammation featured with the local accumulation of inflammatory products in human dental pulps. A GEO dataset GSE16134 comprises data of inflamed dental pulp tissues was used for bioinformatics analyses. A protein-protein interaction (PPI) analysis suggested that chemokine receptor 4 (CXCR4) owned a high correlation with platelet endothelial cell adhesion molecule-1 (PECAM1). A rat model with pulpitis was established, and lipopolysaccharide (LPS)-induced human dental pulp fibroblasts (HDPFs) were used for in vitro experiments. Then, high expression of PECAM1 and CXCR4 was validated in the inflamed dental pulp tissues in rats and in LPS-induced HDPFs. Either downregulation of PECAM1 or CXCR4 suppressed inflammatory cell infiltration in inflamed tissues as well as the inflammation and apoptosis of HDPFs. A transcription factor myocyte-enhancer factor 2 (MEF2C) was predicted and validated as a positive regulator of either PECAM1 or CXCR4, which activated the NF-κB signaling pathway and promoted pulpitis progression. To sum up, this study suggested that MEF2C transcriptionally activates PECAM1 and CXCR4 to activate the B-cell and NF-κB signaling pathways, leading to inflammatory cell infiltration and pulpitis progression.